Pentingnya Eksekusi Kepemimpinan Strategis Dalam Mencapai Tujuan Perusahaan: Chapter Review Dari Buku The Strategic Leader’s Roadmap - Taufiq Rahmat; Taufiq Rahmat (KarismaPro, 2023)
Objective: This article aims to explore the importance of effective strategy execution in achieving organizational goals and draws insights from the case study of H. Lawrence Culp Jr. and the strategy-led execution at Danaher Corporation. The objective is to highlight the key learnings and implications of the study for leaders seeking to enhance their strategic leadership capabilities.Methods: The research employs a case study approach, analyzing the leadership and execution strategies implemented by H. Lawrence Culp Jr. during his tenure at Danaher Corporation. It utilizes secondary data from the book "The Strategic Leader’s Roadmap" by Harbir Singh and Michael Useem, which provides in-depth insights into the strategic leadership practices at Danaher.Results: The study emphasizes the criticality of effective strategy execution in driving organizational performance. By adopting the Danaher Business System (DBS) and incorporating principles from Lean Manufacturing and Six Sigma, Culp successfully transformed the company's culture towards a focus on quality, efficiency, and innovation. This resulted in significant improvements in the company's financial performance, steady revenue growth, and successful expansion through strategic acquisitions.Limitations: The study is based on secondary data and the case of a single organization, Danaher Corporation, which may limit its generalizability to other industries or contexts. Additionally, the study does not explore potential challenges or failures in strategy execution that may have occurred during Culp's leadership at Danaher.Keywords: Danaher Business System (DBS), Strategic Leadership, Organizational Performance, Culture Transformation, Continuous Improvement.